Fishermen Human Rights Protection and Sustainable Development in the Indonesian Marine Sector - Masitha Tismananda Kumala; Ria Tri Vinata; Titik Suharti; Peni Jati Setyowati (Lex Portus, 2023)
Sustainable development is realized in various sectors, including marine and fisheries. Fishermen are the main pillars in advancing the marine and fisheries sector. The welfare of fishermen in Indonesia is not as good as Indonesia’s ambitions in promoting the marine and fisheries sector. One of the Human Rights, namely the right to a decent and prosperous life, still needs to be felt by most small-scale or artisanal fishermen. The purpose of this research is to find a direction for fisheries and marine policies that can protect the human rights of fishermen to realize sustainable development in Indonesia’s marine and fisheries sector. The paper explore two legal issues: Indonesian fishermen’s human rights problems and protecting Indonesian fishermen’s human rights to sustainable development realization in Indonesia’s marine and fisheries sector. Indonesian fishermen’s human rights problems are the right to have a decent and prosperous life, to receive proper and fair treatment in work relations, to obtain legal protection, not to be tortured and enslaved, and the right to adjust the occupation identity written in the National Identification Card (NIC) for the female fishermen. Protecting Indonesian fishermen’s human rights cannot be realized without international cooperation with other states because many Indonesian fishermen work in foreign-flagged vessels. The working conditions in which the majority of fishermen in Indonesia operate, specifically in countries such as China, South Korea, and Taiwan, do not align with several international agreements aimed at safeguarding the rights of fishermen. Finally, the article considers establishing international cooperation between Indonesia and related states to protect fishermen’s human rights.